THE LEVEL OF STUDENTS' SELF-CONFIDENCE IN SPEAKING ENGLISH - Celli Geovani; Aisyah Amru; Ade Aisyah Nazhwandini Panjaitan; Annisa Annisa (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Self-confidence is a crucial factor influencing students' ability to speak English. Students with high self-confidence tend to participate more actively in communication, whereas those with low self-confidence often experience anxiety and hesitation when expressing their ideas. Although the relationship between self-confidence and speaking ability has been widely investigated, empirical evidence describing students' levels of self-confidence in English-speaking contexts remains limited. Therefore, this study aimed to describe students' levels of self-confidence in speaking English. This study employed a quantitative approach using a descriptive research design. The participants consisted of 29 students from the Tadris Bahasa Inggris (TBI) Study Program, selected using total sampling. Data were collected through a 20-item questionnaire and analyzed using descriptive statistics, including mean scores, percentages, and frequency distributions. The findings revealed that the majority of students demonstrated a low level of self-confidence, with an overall mean score of 2.21, while 62.07% of the participants were classified in the low self-confidence category. Students' self-confidence was influenced by vocabulary mastery, pronunciation ability, fear of making mistakes, and classroom environment. These findings suggest that students' self-confidence profiles can serve as an empirical basis for lecturers to design more effective speaking instruction aimed at enhancing students' confidence, classroom participation, and speaking performance. ABSTRAK Kepercayaan diri merupakan faktor penting yang memengaruhi kemampuan siswa dalam berbicara bahasa Inggris. Siswa dengan kepercayaan diri tinggi cenderung lebih aktif berkomunikasi, sedangkan siswa dengan kepercayaan diri rendah sering mengalami kecemasan dan keraguan saat menyampaikan ide. Meskipun hubungan antara kepercayaan diri dan kemampuan berbicara telah banyak dikaji, pemetaan tingkat kepercayaan diri siswa dalam konteks pembelajaran bahasa Inggris masih memerlukan bukti empiris sebagai dasar penyusunan strategi pembelajaran yang lebih tepat. Penelitian ini bertujuan mendeskripsikan tingkat kepercayaan diri mahasiswa dalam berbicara bahasa Inggris. Penelitian ini menggunakan pendekatan kuantitatif dengan desain deskriptif. Partisipan penelitian berjumlah 29 mahasiswa Program Studi Tadris Bahasa Inggris (TBI) yang dipilih menggunakan teknik total sampling. Data dikumpulkan melalui kuesioner yang terdiri atas 20 butir pernyataan dan dianalisis menggunakan statistik deskriptif berupa mean, persentase, dan distribusi frekuensi. Hasil penelitian menunjukkan bahwa sebagian besar mahasiswa memiliki tingkat kepercayaan diri pada kategori rendah dengan nilai rata-rata 2,21 dan persentase 62,07%. Kepercayaan diri mahasiswa dipengaruhi oleh penguasaan kosakata, kemampuan pengucapan, rasa takut melakukan kesalahan, serta lingkungan kelas yang memengaruhi kesiapan mereka untuk berkomunikasi. Penelitian ini menunjukkan bahwa profil kepercayaan diri mahasiswa dapat menjadi dasar empiris bagi dosen dalam merancang strategi pembelajaran berbicara yang lebih efektif sehingga mampu meningkatkan kepercayaan diri, partisipasi kelas, dan performa berbicara mahasiswa.